A Single Nucleotide in Stem Loop II of 5′-Untranslated Region Contributes to Virulence of Enterovirus 71 in Mice - Yeh, Ming-Te; Wang, Shainn-Wei; Yu, Chun-Keung; Lin, Kuei-Hsiang; Lei, Huan-Yao; Su, Ih-Jen; Wang, Jen-Ren (PLOS ONE, 2011)
Background Enterovirus 71 (EV71) has emerged as a neuroinvasive virus responsible for several large outbreaks in the Asia-Pacific region while virulence determinant remains unexplored. Principal Findings In this report, we investigated increased virulence of unadapted EV71 clinical isolate 237 as compared with isolate 4643 in mice. A fragment 12 nucleotides in length in stem loop (SL) II of 237 5′-untranslated region (UTR) visibly reduced survival time and rate in mice was identified by constructing a series of infectious clones harboring chimeric 5′-UTR. In cells transfected with bicistronic plasmids, and replicon RNAs, the 12-nt fragment of isolate 237 enhanced translational activities and accelerated replication of subgenomic EV71. Finally, single nucleotide change from cytosine to uridine at base 158 in this short fragment of 5′-UTR was proven to reduce viral translation and EV71 virulence in mice. Results collectively indicated a pivotal role of novel virulence determinant C158 on virus translation in vitro and EV71 virulence in vivo. Conclusions These results presented the first reported virulence determinant in EV71 5′-UTR and first position discovered from unadapted isolates.